ผลการสอนทบทวนโดยคอมพิวเตอร์ช่วยสอนเรื่อง การบริหารการให้ยาฉีดที่มีต่อความพร้อมในการปฎิบัติการฉีดยาของนักศึกษาพยาบาล - นงค์คราญ เรืองจิตต์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purposes of this quasi-experimental research were to study the effect of using the computer assisted instruction for administering injection medications (CAI-AIM) on injection practice readiness of nursing students. The quasi-experimental research of three-group pretest-posttest design was utilized. Samples were 60 second-year nursing students from Faculty of Nursing, Chiang Mai University. They were matched by the grade obtained from the Fundamental of Nursing course and were randomly assigned into two experimental groups and one control group, 20 in each group. The experimental group I received the tutorial teaching method by the CAI-AIM. The experimental group II received the tutorial teaching method by the teacher and the CAI-AIM. The control group received the tutorial teaching method by the teacher only. The instruments were developed by the researcher and tested for content validity. The instruments consisted of the CAI-AIM program, lesson plan, and the injection practice readiness instrument which was composed of knowlegde and attitude dimensions. Reliability of the knowledge readiness test was .73 and the attitude readiness questionnaire was .87. Data were analyzed by t-test, ANOVA, and Scheffe s method. Major findings were as follows: 1. The injection practice readiness of nursing students after receiving the CAI-AIM totorial teaching was significantly higher than that before receiving the tutorial teaching, at the .05 level. 2. The overall injection practice readiness and the knowledge readiness dimension of nursing students in the groups receiving tutorial teaching by the CAI-AIM and the teacher with CAI-AIM were significantly higher than that by the teacher, at the .05 level. The attitude readiness dimension was not significantly different among the three groups.